METAPHORICAL SEMIOTICS AND THE CRIME SCENE: READING “THE NAME OF THE ROSE” THROUGH THE LENS OF FIGURATIVE LANGUAGE - Ziadi Abdelaaziz,; Mebitil Naouel, (International Journal of Innovative Technologies in Social Science, 2025)
This research explores the integration of metaphor within semiotic frameworks for criminal investigations, mainly as represented in Umberto Eco's The Name of the Rose. Physical traces, viewed as signs, are crucial for solving crimes, and according to Charles Peirce's concept, these indices are causally linked signs. However, this study highlights how metaphor also plays an essential role in the interpretive structure of the narrative. The metaphorical dimension enables a richer understanding of the plot and its philosophical implications. Through a mixed-method approach combining semiotic analysis and literary interpretation, this paper examines crime scenes in the novel, demonstrating how metaphors alongside indices, icons, and symbols enhance investigative reasoning. Ultimately, it argues that metaphors serve as rhetorical devices and epistemological tools that deepen the interpretive process in literature and forensic practice.